1997
DOI: 10.1007/bf00004539
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic influence on gonadotropin secretion in white sturgeon (Acipenser transmontanus)

Abstract: The effects of dopamine on the secretion of two sturgeon gonadotropins (stGTH I and stGTH II) in sexually mature male white sturgeon (Acipenser transmontanus) were evaluated. In Experiment I, sturgeon were given intraperitoneal injections of physiological saline (PS), dopamine (100 mg kg-'), the gonadotropin releasing hormone analog D-Ala 6 -des-Gly 10 -GnRH ethylamide (GnRHA) (10 jig/kg-'), and a combination of GnRHa and dopamine. Fish receiving only GnRHa had significantly higher (p < 0.05) concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…The sperm concentration in milt of four males ranged from 2.9 3 10 8 to 5.4 3 10 9 sperm/mL and was within the range reported for Eurasian and North American sturgeons (Dettlaff et al 1993;Cosson et al 2000;Park and Chapman 2005). Domperidone was used in this study to enhance pituitary response to GnRHa injections, based on the reported dopaminergic inhibition of gonadotropin release in sturgeon (Pavlick and Moberg 1997) and application of dopamine antagonists for induced spawning of other fishes (Peter et al 1988;Dufour et al 2005). With a limited annual supply of broodfish (two pairs), there was a concern that capture and handling stress would affect GnRH-induced ovulation and therefore the annual production of green sturgeon juveniles needed for research projects.…”
Section: Source Of Variation Dfsupporting
confidence: 63%
“…The sperm concentration in milt of four males ranged from 2.9 3 10 8 to 5.4 3 10 9 sperm/mL and was within the range reported for Eurasian and North American sturgeons (Dettlaff et al 1993;Cosson et al 2000;Park and Chapman 2005). Domperidone was used in this study to enhance pituitary response to GnRHa injections, based on the reported dopaminergic inhibition of gonadotropin release in sturgeon (Pavlick and Moberg 1997) and application of dopamine antagonists for induced spawning of other fishes (Peter et al 1988;Dufour et al 2005). With a limited annual supply of broodfish (two pairs), there was a concern that capture and handling stress would affect GnRH-induced ovulation and therefore the annual production of green sturgeon juveniles needed for research projects.…”
Section: Source Of Variation Dfsupporting
confidence: 63%
“…Interestingly, a dopaminergic inhibition of GnRH‐induced pituitary gonadotropin secretion has also been found in a chondrostean fish, the white sturgeon Acipenser transmontanus Richardson (Pavlick & Moberg, 1997). This indicates that the role of DA in the inhibitory control of reproduction may not be specific to teleosts, but may have a more ancient evolutionary origin, in an actinopterygian ancestor, common to teleostean and chondrostean fishes.…”
Section: Inhibitory Role Of Dopamine In the Neuroendocrine Control Ofmentioning
confidence: 91%
“…In teleost, the stimulatory function of GnRH may be inhibited by dopamine though activation of the dopamine D2 receptor and down regulation of GnRH activity by increase in the GnRH-binding capacity whereas treatment with apomorphin, reversed this effect (De Leeuw et al, 1989). The inhibitory role of dopamine was also confirmed in other fish species such as the common carp Cyprinus carpio L., (Peng et al, 1994), African catfish Clarias gariepinus (Burchell, 1822) (De Leeuw et al, 1988), rainbow trout Oncorhynchus mykiss (Walbaum, 1792) (Saligaut et al, 1998) and white sturgeon Acipenser transmontanus (Richardson, 1836) (Pavlic and Moberg, 1997). Dopamine inhibition of GT release was, however, not confirmed in marine species (Copeland and Thomas, 1989).…”
Section: Introductionmentioning
confidence: 63%